Maternal intrapartum pyrexia audit. (16th November 2010) - Darbhamulla, SV; Nakade, M; Pradhan, P
Abstract : Aim: To evaluate adherence to departmental guidelines in management of women with intrapartum fever. Methodology: Retrospective audit performed from January to June 2009. Inclusion criteria was maternal fever over 38° during labour. 42 cases were selected, 36 notes reviewed. According to guideline women with fever over 38°, should have blood cultures along with infectious screen (mid stream specimen of urine for culture and sensitivity, high vaginal swab, full blood count) and to receive intravenous antibiotics for 48 h (Benzyl penicillin, gentamycin, metronidazole). Results: Out of 36 women, 21 laboured spontaneously, labour was induced in 15. 17 women had SROM (spontaneous rupture of membranes), duration varied from 4 to 140 h. 18 women had ARM (artificial rupture of membranes); ARM to delivery interval was 40 min to 25 h. Blood cultures were performed in 28 (77%), and were GBS (Group B streptococcus) positive in two. 16 MSU sent, one GBS positive. Two out of 12 LVS (low vaginal swab) were GBS positive. Antibiotics were given in 23 (63%). 17 (47%) delivered by Emergency LSCS, 15 (41%) vaginal delivery and four had instrument delivery. 28 (77%) women were delivered with in 4 h from temperature spike. In 55% temperature settled with in 4 h. 69% Women were discharged home in 3–4 days. 14 (40%) babies were admitted to neonatal unit. Positive for GBS in two, Escherichia coli in one. Conclusion: Blood cultures were performed in (77%). 63% received antibiotics as per protocol. The authors felt early delivery has contributed to good out come for mothers. There is high morbidity in neonatates 40% admitted to neonatal unit. Audit suggested reducing the duration of intravenous antibiotics to 24 h and to change antibiotic policy.